Tensile properties of composite laminates due to fuel attack - Ishak, Nurul Atiqah (Universiti Sains Malaysia, 2017)
The main purpose of this study is to investigate the effects of kerosene, biofuel, distilled water and room temperature condition on the moisture behavior and mechanical properties of the E-glass reinforced composite. A laminate composite from the E-glass composite material is fabricated that consist from two type of resins which are polyester-based resin and epoxy-based resin. A variety method has been conducting which are the traditional hand layup, resin infusion (RI) and vacuum resin transfer molding. The fiber content for each methods is calculated by using density method and resin burn-off method. The specimens is immersed in the three type of solution and the accuracy of Fick’s Law on moisture diffusion is studied. All specimen were left until it is fully saturated respective to its solution. A tensile test was performed subsequently by using the Universal Tensile Machine (Instron) (UTM). The data obtain from the mechanical test were plotted in a graphical approach by using the tensile stress versus strain graph and average tensile stress bar chart. The data obtained were studied and a comparison of data are being made between both type of resin and also between the three different solutions. It was found that there are no significant change in tensile stress and tensile modulus for all the specimen being immersed in kerosene, biofuel and distilled water and in room condition hence this E-glass fiber reinforced composite can be used in manufacturing the fuel tank structure both in marine and aerospace application.